Peer victimisation and its association with psychological and somatic health problems among adolescents in northern Russia - Stickley, Andrew (BioMed Central, 2013)
BACKGROUND: A growing body of evidence from countries around the world suggests that school-based peer victimisation is associated with worse health outcomes among adolescents. So far, however, there has been little systematic research on this phenomenon in the countries of the former Soviet Union. The aim of this study was to examine the relation between peer victimisation at school and a range of different psychological and somatic health problems among Russian adolescents. METHODS: This study used data from the Social and Health Assessment (SAHA) – a cross-sectional survey undertaken in Arkhangelsk, Russia in 2003. Information was collected from 2892 adolescents aged 12–17 about their experiences of school-based peer victimisation and on a variety of psychological and somatic health conditions. Logistic regression analysis was used to examine the association between victimisation and health. RESULTS: Peer victimisation in school was commonplace: 22.1% of the students reported that they had experienced frequent victimisation in the current school year (girls – 17.6%; boys – 28.5%). There was a strong relationship between experiencing victimisation and reporting worse health among both boys and girls with more victimisation associated with an increased risk of experiencing worse health. Girls in the highest victimisation category had odds ratios ranging between 1.90 (problems with eyes) and 5.26 (aches/pains) for experiencing somatic complaints when compared to their non-victimised counterparts, while the corresponding figures for boys were 2.04 (headaches) and 4.36 (aches/pains). Girls and boys who had the highest victimisation scores were also 2.42 (girls) and 3.33 (boys) times more likely to report symptoms of anxiety, over 5 times more likely to suffer from posttraumatic stress and over 6 times more likely to experience depressive symptoms. CONCLUSION: Peer victimisation at school has a strong association with poor health outcomes among Russian adolescents. Effective school-based interventions are now urgently needed to counter the negative effects of victimisation on adolescents’ health in Russia.